Wind Tunnel Testing and Validation of Helicopter Rotor Blades Using Additive Manufacturing. (21st September 2022) - Hasan, Inamul; Mukesh, R.; Radha Krishnan, P.; Srinath, R.; Babu, Dhanya Prakash; Lemma Gurmu, Negash
Abstract : This research paper aims to validate the aerodynamic performance of rotor blades using additive manufacturing techniques. Wind tunnel testing is a technique used to find the flow characteristics of the body. Computational fluid dynamics (CFD) techniques are used for aerodynamic analysis, and validation should be done using wind tunnel testing. In the aerodynamic testing of models, additive manufacturing techniques help in validating the results by making models easily for wind tunnels. Recent developments in additive manufacturing help in the aerodynamic testing of models in wind tunnels. The CFD analysis of helicopter rotor blades was analyzed in this research, and validation was done using additive manufacturing techniques. Computational analysis was carried out for static analysis for the forward speeds of Mach numbers 0.3, 0.4, and 0.5. The results obtained were satisfactory to the previous results and were validated with wind tunnel testing. Results proved that the error percentage was lower, and the computational analysis was valid. In this research, models were designed using the FDM technique for wind tunnel testing as it is cost-effective and easy to manufacture.